Microstructure characterization and hot corrosion mechanism of as-cast and heat treated high Nb containing TiAl alloy. (June 2021) - Sun, Zhiping; Wu, Wenqing; Chen, Yongnan; Yuan, Zhanwei; Zhang, Yongshuai; Guo, Xiping
Highlights: As-cast Ti-44Al-9Nb-0.5Si (TA1) and Ti-44Al-9Nb-0.5Si-0.3Y (TA2) were mainly composed of α2 +γ lamellae. The addition of 0.3Y reduced lamellar colony and lamellar thickness in TA2. Comparing to TA1, TA2 had better hot corrosion resistance due to its denser scale on finer lamellar colony. Based on vertical section precise Tα and Te were obtained, and multi-step heat treatment was conducted. After heat treatment, γ grains, α2 grains and Ti5 (Si, Al)3 precipitations appeared in TiAl alloys. Abstract: TiAl alloys possess broad development prospects in aerospace industry. To characterize hot corrosion behavior in service environment and provide comprehensive assessment of high Nb containing TiAl alloys, microstructure evolution and hot corrosion mechanism of them were focused. Ti-44Al-9Nb-0.5Si (TA1) and Ti-44Al-9Nb-0.5Si-0.3Y (TA2) solidified via β phase; β/α transformation took place after β solidification; α was finally deposed to α2 +γ lamellae. Compared with TA1, TA2 had better hot corrosion resistance due to its finer lamellar structure. Based on Ti-Al-9Nb-0.5Si vertical section, heat treatment was conducted. After heat treatment, equiaxed γ grains, α2 grains and Ti5 (Si, Al)3 precipitations appeared.